The word baptizo defined: and the mode of baptism proved from the scriptures - Hall, John H. (Weare C. Little, 1840)
(from t.p.) Part 1. The mode of baptism -- Part 2. Scriptural qualifications necessary for baptism -- Part 3. Infant baptism compared with the Scriptures.